Analisis Kelayakan Buku Teks Bina Belajar Al-Qur’an dan Hadits Kelas V Pada Kurikulum Madrasah Tahun 2019 dalam Pembelajaran Abad 21 - Annisa Mardiah; Fadhil Abu Jihad (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
In the book Bina Belajar Al-Qur'an dan Hadith for grade V MI published by Erlangga Publisher in accordance with the madrasah curriculum (KMA) No. 183 of 2019, this book is analyzed by researchers in meeting the needs of 21st century learning, especially in developing critical thinking skills, creativity, communication, and collaboration. This study aims to analyze the feasibility of textbooks based on four aspects of the National Education Standards Agency (BSNP) standards, namely the feasibility of content, feasibility of presentation, language and graphics. This study uses a literature study approach (library study) which is used to collect various data sources from the book Bina Belajar Al-Qur'an dan Hadith, journals and others. The results of the study show that this book is in the very feasible category, with the suitability of the material to KMA No. 183 of 2019, the use of communicative language, and consistent graphic displays. However, deficiencies were found in the presentation aspect, such as the absence of concept maps, learning objectives, and the lack of contextual illustrations. Overall, this book remains relevant and can support the learning of the Qur'an and Hadith in MI.